Plant-parasitic nematodes associated with banana (MUSA SPP.) in Rusitu valley, Zimbabwe - Chitamba, James; Manjeru, Pepukai; Chinheya, Cleopas Chenai; Mudada, Nhamo; Handiseni, Maxwell (Nematropica, 2021)
Banana is one of the most important food and cash crop in Zimbabwe as well as in the world. Plant-parasitic nematodes are one of the major constraints of banana production and are therefore a threat to food security. A eld survey to quantify and classify plant-parasitic nematodes associated with banana was conducted in Rusitu Valley, which is one of the major smallholder banana production areas of Zimbabwe. Plant-parasitic nematodes were surveyed from soil and banana roots collected from forty smallholder banana farms. Meloidogyne spp., Radopholus similis, Pratylenchus spp. and Helicotylenchus spp. were the major plant-parasitic nematodes associated with banana plants in Rusitu Valley. In terms of absolute frequencies, Meloidogyne, Radopholus, Pratylenchus, followed by Helicotylenchus were the most frequently found genera throughout the soil assay. However, Meloidogyne was the most abundant whilst Radopholus the least in terms of total number of nematodes in soil in all the sampled elds.